MicroRNA-210-5p Contributes to Cognitive Impairment in Early Vascular Dementia Rat Model Through Targeting Snap25 - Ren, Zhenxing; Yu, Junlong; Wu, Zimei; Si, Wenwen; Li, Xianqian; Liu, Yuqing; Zhou, Jianhong; Deng, Rudong; Chen, Dongfeng (Frontiers in Molecular Neuroscience, 2018)
Vascular dementia (VD) is the most common form of dementia in the elderly. However, little is understood about the role of microRNAs (miRNAs) involved in cognitive impairment in early VD. Here, VD model induced by chronic cerebral ischemia and FBS-free cell model detecting synapse formation were established to investigate the function of microRNAs in early VD. Microarray analysis and real-time reverse transcription PCR showed that miR-210-5p increased significantly in the hippocampus of rat with 4 weeks ischemia. VD model rats also displayed significant cognitive deficits and synaptic loss. Overexpression of miR-210-5p decreased the synaptic number in primary hippocampal neurons. In contrast, specific suppression of miR-210-5p resulted in formation of more synapses. Additionally, intracerebroventricular injection of mir-210-5p agomir to VD rats aggravated phenotypes of cognitive impairment and synaptic loss. These VD-induced phenotypes were effectively attenuated by mir-210 antagomir. Moreover, bioinformatic prediction revealed that Snap25 mRNA is targeted by miR-210-5p. miR-210-5p decreased the luciferase activities of 3’ UTR of Snap25 mRNA. Mutation of predicted miR-210-5p binding sites in the 3’ UTR of Snap25 mRNA abolished the miR-210-5p induced decrease in luciferase activity. Western blot and immunofluorescence staining confirmed that miR-210-5p targets on Snap25. Finally, detected by RT-qPCR and immunofluorescence staining, miR-210-5p agomir downregulated Snap25 expression in CA1 region of VD rats’ hippocampi, in contrast, miR-210-5p antagomir upregulated Snap25 expression. Taken together, miR-210-5p contributes to cognitive impairment in chronic ischemia-induced VD model through regulation of Snap25 expression, which potentially offer the opportunity to develop a new therapeutic strategy for VD.